2016
DOI: 10.1590/0074-02760150359
|View full text |Cite
|
Sign up to set email alerts
|

Primary dengue virus infections induce differential cytokine production in Mexican patients

Abstract: Severe dengue pathogenesis is not fully understood, but high levels of proinflammatory cytokines have been associated with dengue disease severity. In this study, the cytokine levels in 171 sera from Mexican patients with primary dengue fever (DF) and dengue haemorrhagic fever (DHF) from dengue virus (DENV) 1 (n = 116) or 2 (n = 55) were compared. DF and DHF were defined according to the patient’s clinical condition, the primary infections as indicated by IgG enzymatic immunoassay negative results, and the inf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
23
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(27 citation statements)
references
References 42 publications
4
23
0
Order By: Relevance
“…Fifty-six studies were included in this meta-analysis. The authors of forty-nine studies were contacted for unpublished data, and two sets of authors, Eppy et al (2016) and De la Cruz Hernández et al (2016) , responded to provide their unpublished data. These two studies were also included.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Fifty-six studies were included in this meta-analysis. The authors of forty-nine studies were contacted for unpublished data, and two sets of authors, Eppy et al (2016) and De la Cruz Hernández et al (2016) , responded to provide their unpublished data. These two studies were also included.…”
Section: Resultsmentioning
confidence: 99%
“…In vitro studies have found no structural damage or cell death in infected endothelial cells ( Chaturvedi et al, 2000 ; Srikiatkhachorn et al, 2006 ). Moreover, differences in levels of cytokines and chemokines were found when sera/plasma samples from dengue hemorrhagic fever (DHF) and dengue fever (DF) patients were compared ( De la Cruz Hernández et al, 2016 ), which suggests that severe symptoms are caused by the cytokines and chemokines that act as mediators and vasodilators in blood, rather than by direct virus-induced cell damage. This hypothesis also explains the observation that severe symptoms occur during defervescence, after the decrease of viremia ( Dejnirattisai et al, 2008 ).…”
Section: Introductionmentioning
confidence: 99%
“…Lipid metabolism is extensively regulated by cytokines during the host response to infection . TNF‐α is a key pro‐inflammatory cytokine that has been associated with many biological functions such as lipid metabolism; it is well known that DF and DHF patients have significantly higher levels of pro‐inflammatory cytokines …”
Section: Discussionmentioning
confidence: 99%
“…[ 4 ] The phenomena of original antigenic sin, [ 6 ] immune evasion that inhibits interferon (IFN)-α and IFN-β signaling by suppressing Jak-Stat activation, [ 7 ] a cytokine storm, [ 8 ] and autoimmune responses [ 9 ] are thought to contribute to the pathogenesis of severe form of dengue disease. However, contradictory findings have been proposed by Hernández et al, [ 10 ] where no significant association was observed between the level of proinflammatory cytokines and disease severity, reflecting the complex nature of pathophysiology of dengue disease.…”
Section: Introductionmentioning
confidence: 89%